(untitled) (Texas Journal of Medical Science, 2025)
Blood enzymes are key biochemical components of the body, participating in many vital processes, including metabolism, regulation of many physiological functions and reactions to changes in external factors. One of the significant influencing factors is the impact of ambient temperature, as well as the level of insolation, that is, the amount of solar radiation reaching the body’s surface. With changes in external temperature, blood enzymes exhibit different activity. The activation or inhibition of biochemical reaction chains can be caused by both the temperature sensitivity of the enzymes themselves and changes in the body’s internal homeostasis. However, excessive heating can also lead to protein denaturation, which seriously limits enzyme functionality. Insolation, in turn, can influence enzyme synthesis and activity through mechanisms associated with ultraviolet radiation